Electrical characterization of metal-oxide-polymer devices for non-volatile memory applications - Rocha, Paulo R. F. (2015)
The objective of this thesis is to study the properties of resistive switching effect based on bistable resistive memory which is fabricated in the form of Al2O3/polymer diodes and to contribute to the elucidation of resistive switching mechanisms. Resistive memories were characterized using a variety of electrical techniques, including current-voltage measurements, small-signal impedance, and electrical noise based techniques. All the measurements were carried out over a large temperature range. Fast voltage ramps were used to elucidate the dynamic response of the memory to rapid varying electric fields. The temperature dependence of the current provided insight into the role of trapped charges in resistive switching. The analysis of fast current fluctuations using electric noise techniques contributed to the elucidation of the kinetics involved in filament formation/rupture, the filament size and correspondent current capabilities. The results reported in this thesis provide insight into a number of issues namely: (i) The fundamental limitations on the speed of operation of a bi-layer resistive memory are the time and voltage dependences of the switch-on mechanism. (ii) The results explain the wide spread in switching times reported in the literature and the apparently anomalous behaviour of the high conductance state namely the disappearance of the negative differential resistance region at high voltage scan rates which is commonly attributed to a “dead time” phenomenon which had remained elusive since it was first reported in the ‘60s. (iii) Assuming that the current is filamentary, Comsol simulations were performed and used to explain the observed dynamic properties of the current-voltage characteristics. Furthermore, the simulations suggest that filaments can interact with each other. (iv) The current-voltage characteristics have been studied as a function of temperature. The findings indicate that creation and annihilation of filaments is controlled by filling and neutralizing traps localized at the oxide/polymer interface. (v) Resistive switching was also studied in small-molecule OLEDs. It was shown that the degradation that leads to a loss of light output during operation is caused by the presence of a resistive switching layer. A diagnostic tool that predicts premature failure of OLEDs was devised and proposed. Resistive switching is a property of oxides. These layers can grow in a number of devices including, organic light emitting diodes (OLEDs), spin-valve transistors and photovoltaic devices fabricated in different types of material. Under strong electric fields the oxides can undergo dielectric breakdown and become resistive switching layers. Resistive switching strongly modifies the charge injection causing a number of deleterious effects and eventually device failure. In this respect the findings in this thesis are relevant to understand reliability issues in devices across a very broad field.